Estudo comparativo da qualidade da água dos reservatórios fluviais de marés e Gramame-Mamuaba na Paraíba - Silva, João Carlos de Miranda e (2018)
The Reservoirs of Marés and Gramame-Mamuaba are the most important water sources that supply João Pessoa and the metropolitan region. In addition to human supply, other uses may, although legally assured (Law N°. 9,433/97), present a potential risk to water quality. The present work aims to make a comparison between the water quality of the two reservoirs, for that, a field survey of the situation of the springs was carried out, analysis of the water quality monitoring data carried out by the Environmental Administration Superintendence (SUDEMA), as well as research on published material. With reference to monitoring data, the first series analyzed (2005-2008) evaluated 8 physicochemical parameters (Temperature, Color, pH, Turbidity, Electrical Conductivity, Dissolved Oxygen, Biochemical Oxygen Demand) and Microbiological (Thermotolerant Coliforms), With the monthly sampling it was possible to make inferences about the monthly averages and the differences between the seasonal periods (of higher and lower rainfall), besides verifying the legal limits as to the pertinent legislation. And in a second period (2007-2017), when there were changes in the methodology of SUDEMA, such as sampling to be semiannual, and other measurements such as: Total Residue, Nitrogen and Total Phosphorus, compiling them through the Quality Index of the SUDEMA. Waters (IQA). The results showed similar monthly variations in the first data series for temperature, Color, pH, OD and Coliform parameters, but between seasonal periods the similarity is present in temperature, color, OD, BOD and coliforms. In the same period, nonconformities were found for Color, OD, BOD and Thermotolerant Coliforms. The IQA presented the good qualification present in most of the monitored period for both reservoirs, on the other hand, the parameters that compose the IQA Turbidity presented a negative trend, while the Total Phosphorus and Thermotolerant Coliforms showed a worrying positive trend. In Marés it was found a greater number of non-conformities with the legislation and with lower WQI values, the physical-chemical parameters also showed greater variation. Another finding was the numerous problems found around the reservoirs that may present a risk of water quality degradation.